Efficacy and safety of a modified- 'modified Ponticelli' regimen for treatment of primary membranous nephropathy - Indu Ramachandra Rao; Ravindra Prabhu Attur; Dharshan Rangaswamy; Srinivas Shenoy; Sindhura Lakshmi Koulmane Laxminarayana; Shankar Prasad Nagaraju (Society of Diabetic Nephropathy Prevention, 2019)
Background: Modified Ponticelli regimen (mPR), consisting of cyclical steroids and cyclophosphamide, is the most established therapy for primary membranous nephropathy (MN). Yet, the potential toxicity of this treatment regimen poses a significant concern. Objectives: The aim of this study was to assess the efficacy and safety of a modified version of the conventional mPR for primary MN using lower-than-standard dose pulse steroids. Patients and Methods: This was a retrospective single-center analysis of patients admitted between January 2008 to December 2017. All treatment-naive patients with biopsy-proven primary MN treated with a lower-than-standard dose pulse steroid-based modification of the conventional mPR (intravenous pulse of 500 mg methyl-prednisolone, instead of 1000 mg) were included. We report the remission rates at the end of 6 months (both complete and partial), relapses and adverse effects of treatment at the end of follow-up. Results: A total of 41 individuals were included. Of 31 individuals who completed six months of treatment (six were lost to follow-up, while four discontinued immunosuppression due to infections), 71% (n=22) responded to treatment [complete remission in 25.8% (n=8), partial remission in 45.2% (n=14)]. Most common complications detected throughout the treatment were steroid induced diabetes mellitus in 40% (n=14/35), infections in 25.7% (of which immunosuppression was discontinued for four participants), and leucopenia in 8.5% (n=3/35). Relapses were seen in 29% (n=9) during follow-up (mean follow-up period: 36 months). Conclusions: The modified- 'modified Ponticelli' regimen with lower-than-standard dose intravenous steroids and cyclophosphamide was efficient in attaining remission in primary MN.